Prostate Cancer Biomarker Detection with Carbon Nanotubes Modified Screen Printed Electrodes. Issue 5 (21st December 2015) - Nur Topkaya, Seda; Ozkan‐Ariksoysal, Dilsat
Abstract: DNA hypermethylation is an epigenetic alteration and a promising biomarker for early prostate cancer detection. Simple, sensitive, easy to handle and rapid detection methodologies are imperative for point of care diagnostics especially for cancer. Herein, we describe for the first time a regenerable and compatible electrochemical biosensor for detection of Glutathione S‐Transferase P‐1 ( GSTP‐1) gene hypermethylation related to prostate cancer via DNA hybridization onto the disposable Carbon and Multi Walled Carbon Nanotubes (MWCNT) Screen Printed Electrodes (SPEs). In the study, capture probes were adsorbed onto the SPEs by simple passive adsorption and then hybridization was achieved by sending the complementary target onto the probe‐modified electrodes. The selectivity of the biosensor was proved by control studies. Differential Pulse Voltammetry (DPV) technique was used to detect hybridization via guanine oxidation signals changes. The total time of the optimized method was nearly 1h, measurements took for less than 1 min, and the biosensor response was stable up to 40 days of storage period at 4 °C. The main advantages of the biosensor are very low detection limit (picomolar range) and capability of reusing the biosensor for at least 3 times after very simple regeneration process that is a unique property to reduce the cost of the assay. In addition, this is the first study that demonstrates the detection of GSTP‐1 hypermethylation electrochemically by using SPEs in order to create point of care diagnostics. The optimum parameters for the biosensor, as well as its future prospects to enhance the performance of DNA biosensors were also presented. Abstract :